Turbine Slope Testing in Microhydro Plants as a Regional Electricity Source near River Flows that are not Reachable by PLN: Muhammad Arief Bustomi, Meli Riski Utami, Bachtera Indarto, Yono Hadi Pramono, Gontjang Prajitno, Ali Yunus Rohedi, Endah Purwanti - Muhammad Arief Bustomi; Meli Riski Utami Utami; Bachtera Indarto Indarto; Yono Hadi Pramono Pramono; Gontjang Prajitno Prajitno; Ali Yunus Rohedi Rohedi; Endah Purwanti Purwanti (Jurnal Fisika dan Aplikasinya, 2025)
Electrical energy has become the main need of society. PLN manages the supply of electrical energy in Indonesia as the State Electricity Company. The problem is that not all areas of Indonesia are covered by the PLN electricity network. Various energy sources can be converted into electrical energy in remote areas not yet reached by the PLN network. One example of this energy source is micro hydro energy, energy from river flows that are not too strong. The equipment for converting micro hydro energy into electrical energy is called MHPP. This research is part of the application of MHPP based on Archimedes screw turbines as a source of electricity for areas near river flows that are not yet accessible to river flows. The focus of the research is to study the effect of the turbine elevation angle on the output electrical power of the MHPP. This research aims to determine the optimum values of rotation, torque, voltage, current and electrical power produced by an Archimedes screw turbine MHPP design with variations in turbine elevation angles of 20°, 25°, 30°, 35° and 40°. The MHPP design studied consists of 3 blades, a gearbox ratio of 2.8:1, a water flow rate of 6.34 liters/second, and a low rpm BLDC generator type. The optimum rotation is 1001.38 rpm at an elevation angle of 35° and the optimum torque is 1,738 Nm at an elevation angle of 40°. The optimum voltage is 14.84 V, the optimum current is 0.670 A, and the optimum electrical power is 7.861 W at an inclination angle of 40°.